Sewage-and fertilizer-derived nutrients alter the intensity, diversity, and toxicity of harmful cyanobacterial blooms in eutrophic lakes - Gobler, Christopher J.; Drinkwater, Ruth W.; Anthony, Alexander; Goleski, Jennifer A.; Famularo-Pecora, Ann Marie E.; Wallace, Marcella Kretz; Straquadine, Nora R. W.; Hem, Ronojoy (Frontiers in Microbiology, 2024)
Cyanobacterial harmful algal blooms (CHABs) are promoted by excessive nutrient loading and, while fertilizers and sewage are the most prevalent external nutrient sources in most watersheds, the differential effects of these nutrient sources on CHABs are unknown. Here, we tracked CHABs and performed experiments in five distinct lakes across the Northern US including Lake Erie. Fertilizers with ammonium and orthophosphate, membrane (0.2 μm)-filtered sewage (dominated by reduced forms of nitrogen) sand-and membrane-filtered sewage (dominated by nitrate), and an inorganic nutrient solution of ammonium and orthophosphate were used as experimental nutrient sources for CHABs at N-equivalent, environmentally realistic concentrations. Phytoplankton communities were evaluated fluorometrically, microscopically, and via high throughput sequencing of the 16S rRNA gene, and levels of microcystin and the δ15N content of particulate organic nitrogen (δPO15N) were quantified. Fertilizer and both sources of wastewater increased the abundance of cyanobacteria in all experiments across all five lakes (p < 0.05 for all) whereas effects on eukaryotic phytoplankton were limited. Sand-filtered sewage contained less P, organic matter, and ammonium but more nitrate and had a 25% less potent stimulatory effect on cyanobacteria than membrane-filtered sewage, suggesting nitrification may play a role in reducing CHABs. Fertilizer increased microcystin levels and decreased the δPO15N whereas wastewater increased δPO15N (p < 0.05 for all). Microcystis was the genus most consistently promoted by nutrient sources (p < 0.05 in all experiments), followed by Cyanobium (p < 0.05 in 50% of experiments), with increases in Microcystis biomass consistently elicited by membrane-filtered wastewater. Collectively, results demonstrate that differing types of sewage discharge and fertilizers can promote CHAB intensity and toxicity, while concurrently altering CHAB diversity and δPO15N. While membrane-filtered sewage consistently favored Microcystis, the discharge of sewage through sands muted bloom intensity suggesting sand-beds may represent a tool to remove key nutrients and partially mitigate CHABs.